Peningkatan Literasi Penggunaan Obat melalui Edukasi Pengenalan Logo Obat bagi Siswa SMP Muhammadiyah 04 Pangkatrejo - Aditya Sindu Sakti; Bheta Sari Dewi; Nurul Izzah H. L. Pasi; Marhamah Marhamah; Amalia Puspa Wahyu; Deta Hilar Nurrohmah; M. Ahsanul Farihin; Nur’aini Al Wahida (Pusat Riset dan Inovasi Nasional, 2025)
This community service program aimed to enhance students’ pharmaceutical literacy through the introduction of drug classification logos at SMP Muhammadiyah 04 Pangkatrejo. The background of this activity was the low level of drug-use literacy among adolescents, often leading to irrational self-medication. The activity employed a quantitative descriptive design with a one-group pretest–posttest approach. Educational interventions included interactive counseling, PowerPoint presentations, visual media using logo sticks, and pretest–posttest evaluation. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant improvement in students’ knowledge (p = 0.000), with mean scores increasing from 58% to 81% after the intervention. The highest gain was observed in the recognition of logo colors and drug classifications. Satisfaction analysis revealed that 96% of participants expressed satisfaction with the learning process, especially regarding material clarity and the presenters’ readiness to answer questions. The study concludes that participatory educational methods and visual media effectively improve rational drug-use awareness among junior high school students. Future programs are recommended to expand similar activities to other schools and integrate digital media for sustained impact on public health literacy.